Percentile curves for the knee injury and osteoarthritis outcome score in the middle-aged Dutch population. Issue 8 (August 2020) - Loef, M.; Kroon, F.P.B.; Böhringer, S.; Roos, E.M.; Rosendaal, F.R.; Kloppenburg, M.
Summary: Objective: To improve the interpretation of the Knee injury and Osteoarthritis Outcome Score (KOOS) in individual patients, we explored associations with age, sex, BMI, history of knee injury and presence of clinical knee osteoarthritis, and developed percentile curves. Methods: We used cross-sectional data of middle-aged individuals from the population-based Netherlands Epidemiology of Obesity (NEO) study. Clinical knee osteoarthritis was defined using the ACR classification criteria. KOOS scores were handled according to the manual (zero = extreme problems, 100 = no problems). Patient characteristics associated with KOOS were explored using ordered logistic regression, and sex and body mass index (BMI)-specific percentile curves were developed using quantile regression with fractional polynomials. The curves were applied as a benchmark for comparison of KOOS scores of participants with knee osteoarthritis and comorbidities. Results: The population consisted of 6, 643 participants (56% women, mean (SD) age 56(6) years). Population-based KOOS subscale scores (median; interquartile range) near optimum: pain (100;94–100), symptoms (96;86–100), ADL function (100;96–100), sport/recreation function (100;80–100), quality of life (100;75–100). Worse KOOS scores were observed in women and in participants with higher BMI. Clinical knee osteoarthritis was defined in 15% of participants, and was, in comparison to other patient characteristics, associated with the highest odds of worse KOOS scores. Furthermore, presence of any comorbidity and cardiovascular disease specifically, was associated with worse KOOS scores, particularly in women. Conclusions: In the middle-aged Dutch population KOOS scores were generally good, but worse in women and with higher BMI. These percentile curves may be used as benchmarks in research and clinical practice.